The inverse of the conditional statement can be made by negating both the hypothesis and the conclusion
The inverse of ur conditional statement is : If my mom does not have to work, then I will not babysit my little sister.
Answer:
dddddddddddddddddddddddddddd
9514 1404 393
Answer:
f(x) = -1/3x +23/3
Step-by-step explanation:
You can use the linear regression function of a graphing calculator or spreadsheet to show you the equation of the line through these points:
f(x) = -1/3x +23/3
__
Approaching this in the usual way, we recognize we have points ...
(-1, 8) and (5, 6)
The slope of the line through those points is ...
m = (y2 -y1)/(x2 -x1)
m = (6 -8)/(5 -(-1)) = -2/6 = -1/3
Then the point-slope equation of the line is ...
y - 8 = -1/3(x +1)
Adding 8 gives us a form we can use for a function definition:
f(x) = -1/3(x +1) +8
f(x) = -1/3x +7 2/3
Answer:
Let's call:
f = price of 1 cup of dried fruit
a = price of 1 cup of almonds
In order to build the linear system, you need to consider that the total price of a bag is given by the sum of the price of cups times the number of cups in each bag, therefore:
Solve for a in first equation:
a = (6 - 3f) / 4
Then substitute in the second equation:
41/2 f + 6 · (6 - 3f) / 4 = 9
41/2 f + 9 - 9/2 f = 9
16 f = 0
f = 0
Now, substitute this value in the formula found for a:
a = (6 - 3·0) / 4
= 3/2 = 1.5
Hence, the cups of dried fruit are free and 1 cup of almond costs 1.5$
Step-by-step explanation:
Answer:
en cada vaso debe verter 237 mililitros
Step-by-step explanation:
1896 Divídelo en 8 es igual que 237 por 8